Association Between Dietary Fiber Intake and Heart Failure Among Adults: National Health and Nutrition Examination Survey 2009–2018 - Zhang, Hao; Lin, Zhibin; Chen, Jun; Gan, Daojing; Zhou, Haobin; Ma, Zhuang; Zeng, Xianghui; Xue, Yuting; Wang, Xiao; Zhan, Qiong; Zeng, Qingchun; Xu, Dingli (Frontiers in Cardiovascular Medicine, 2022)
Objective To explore the association between dietary fiber and heart failure (HF). Methods Data were collected from the 2009–2018 National Health and Nutrition Examination Survey. Dietary fiber intake data were obtained from two 24-h dietary recall interviews. Logistic regression and restricted cubic spline models were used to explore the association of dietary intakes of total, cereal, fruit, and vegetable fiber with HF prevalence. Results A total of 21869 adults were included in this study. After adjusting for multiple confounding factors, the odds ratios (OR) and 95% confidence intervals (CI) for HF was 0.49 (0.28 to 0.87, P for trend = 0.016) for the highest tertile versus lowest tertile of total fiber intake. Similar results were observed for cereal but not fruit and vegetable fiber intake. Dose-response analysis indicated that dietary intake of total and cereal fiber were inversely associated with HF in a linear manner. Conclusion Intakes of total and cereal fiber were inversely associated with HF in adults.